B cells latently infected with murine gammaherpesvirus 68 (MHV‐68) are present in the mouse thymus–A step toward immune evasion?. Issue 2 (10th December 2018) - Yamano, Tomoyoshi; Steinert, Madlen; Steer, Beatrix; Klein, Ludger; Hammerschmidt, Wolfgang; Adler, Heiko
Abstract : We show that latently gammaherpesvirus‐infected B cells are present in the thymus. This could result in a functional T‐cell tolerance against certain viral epitopes. It is conceivable that also antigens from other viruses or pathogens may be conveyed to the thymus for their immune evasion.